2022
DOI: 10.1155/2022/9086540
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic Value of Lactate Dehydrogenase, Melanoma Inhibitory Protein, and S-100B Protein in Patients with Malignant Melanoma

Abstract: Objective. This investigation probed the prognostic potential for lactate dehydrogenase (LDH), melanoma inhibitory activity protein (MIA), and S-100B protein in cases of malignant melanoma. Methods. 84 cases were segregated into effective cohort (n = 64) and ineffective cohort (n = 20) depending on clinical efficacy. The cases were followed up for three years and segregated into mortality cohort (n = 29) and survival cohort (n = 55) depending upon 3-year survival. Serum LDH, MIA, and S-100B levels were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Similar results were reported by various other authors [159][160][161]. Furthermore, increased MIA levels are significantly associated with decreased survival [158,162]. Moreover, MIA levels have also been correlated with melanoma recurrence [163].…”
Section: Melanoma-inhibiting Activitysupporting
confidence: 86%
“…Similar results were reported by various other authors [159][160][161]. Furthermore, increased MIA levels are significantly associated with decreased survival [158,162]. Moreover, MIA levels have also been correlated with melanoma recurrence [163].…”
Section: Melanoma-inhibiting Activitysupporting
confidence: 86%
“…The molecule belongs to a family that comprises four members: MIA, MIA2, TANGO (transport and Golgi organization protein 1), and OTOR (otoraplin), with 34–45% of amino acid structure homology and 47–59% of cDNA sequence homology [ 31 ]. MIA is expressed in melanoma cells, and its soluble form is considered a valuable biomarker for the evaluation of melanoma progression [ 14 , 32 ]. MIA is involved in the detachment of melanoma cells from the extracellular matrix (ECM), inhibiting their attachment to fibronectin and laminin and promoting cell migration and invasion.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%